P16.07 Prior condyloma and syphilis diagnosis among hiv-infected persons: a nationwide population-based study in taiwan, 2000–2010. (13th September 2015) - Strong, C; Zou, H; Chen, Y; Li, C; Ko, W; Ko, N
Abstract : Introduction: Previously acquired sexually transmitted infections (STIs) increase the risk of HIV infection, yet few studies have examined the time interval between prior condyloma/syphilis diagnosis and HIV infection. We aimed to examine numbers of condyloma/syphilis diagnosis, and HIV screening prior to HIV infection in relation to HIV risk among HIV-infected persons. Methods: This population-based study retrieved medical claims data from Taiwan National Health Insurance Research Database (NHIRD) from 2000 to 2010 and included 16119 HIV-infected persons more than 15 years of age. We included cases with prior condyloma/syphilis diagnosis before HIV infection and described the elapsed time between first condyloma/syphilis in the database and HIV infection. A subgroup analysis was conducted for those who have prior condyloma/syphilis diagnosis, using multivariable Cox proportional hazard regression to examine factors associated with HIV infection within 1 year. Results: One hundred and fifty-two HIV-infected persons received condyloma diagnosis prior to HIV infection with an average elapsed time of 644 days. Among them, 31% became HIV-infected within one year after first diagnosis of condyloma in the database. For syphilis, 833 persons received syphilis diagnosis and the average elapsed time was 1025 days. Among them, 24% became HIV-infected within one year. For those who have been diagnosed with condyloma, each increment of condyloma diagnosis before HIV infection was associated with an 2.8 times of risk for HIV infection within 1 year (95% confidence interval (CI) = 1.26–6.19). For those who were diagnosed with syphilis, numbers of condyloma and syphilis diagnosis and HIV screening were significantly associated with increased risk of HIV infection within 1 year, with adjusted hazard ratios (aHRs) of 3.97 (1.69–9.32), 1.95 (1.31–2.89), 1.72 (1.53–1.93), respectively. Conclusion: History of condyloma/syphilis before HIV infection was associated with risk of HIV infection among HIV-infected persons. More regular HIV screening among persons with STIs are warranted. Disclosure of interest statement: The authors declare that there are no conflicts of interest.